Increasing Ethical Understanding of the Use of Information Technology Through Digital Literacy Proficiency Training - Erni Krisnaningsih; Saleh Dwiyatno; Ahmad Dedi Jubaedi; Adhe Shafitri (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Since the beginning of the 21st century, the development of information technology in the world has continued to develop massively. Hootsuite and We Are Social as of January 2020 as many as 59% of the world's population can already access the Internet. A similar phenomenon occurs also in Indonesia. In the same survey, Hootsuite estimated that the internet is already accessible to 64% of Indonesians, or around 175.4 million people. Meanwhile, a survey conducted by the Indonesian Internet Service Providers Association (APJII) in the second quarter of 2020 showed that internet penetration in Indonesia reached 73.7% or was already accessible to 196.71 million Indonesians (APJII, 2020). The high number of digital viewers has an impact on the increasing number of users of digital services and changes in people's lifestyles. In terms of practicality and efficiency, it is the reason for accessing information. But behind all the sophistication that exists in today's digital world, it certainly has a positive and negative impact on humans. Understanding of proficient ethics Digital literacy is needed as a reference in the use of technology that is growing to be more targeted. The purpose of community service activities (PKM) is to increase understanding of the ethics of using information technology through digital literacy skills training for the community based on digital safety aspects. Training to increase understanding and application of digital literacy ethics will allow the younger generation to participate in today's modern world era. The training was carried out in 3 sub-districts in Serang Regency with a total number of training participants of 172 participants with resources sharing, mentoring, and workshop method approach. Activities (PKM) consist of 5 stages, namely 1). Problem Identification Stage; 2). Preparation of PKM programs; 3) Pkm team debriefing; 4) implementation of PKM and 5). Evaluation based on pretest and posttest questionnaires. The results of the evaluation of PKM activities based on the digital security pillar have increased understanding of the ethics of trainees from the aspect of digital security based on 5 indicators.